Response rates in studies of couples coping with cancer: a systematic review - Dagan, Meirav; Hagedoorn, Mariët (Health psychology, 2014)
Recruiting couples for psychological studies can be challenging. This brief report is the first to examine the average couples' response rate and to systematically review the quality of reporting of couples' response rate in studies of couples coping with cancer. A systematic review (1980-2011) was conducted, including 83 studies meeting the inclusion criteria of being published in peer-reviewed journals, describing quantitative findings using a cross-sectional or longitudinal design. Overall reporting was unsatisfactory in more than half of the included studies. As a consequence, the couples' response rate (CRR; all analyzed couples divided by the number of eligible partnered patients/couples approached) could be calculated for only 33 samples. This CRR varied considerably across studies from 25% to 90% (CRRM = 58%, SD = 17%). The rates reported in the articles (M = 65%) were often higher than the average CRR (CRRM = 57%) of these samples. This systematic review revealed incomplete reporting of response rate. Therefore, it cannot be firmly concluded that the average CRR reported is representative for all studies on couples coping with cancer. Finally, the figures presented, which are often more favorable than the CRR, may create the impression that the sample is more representative of the target population than it actually is. This has consequences for implementing the findings of such studies into practice. The results are critically discussed, and recommendations for improvement are provided.